Pengaruh Penganggaran Partisipatif Dan Asimetri Informasi Terhadap Budgetary Slack Dengan Moral Equity Sebagai Variabel Moderasi - Salman Hafidz Iriansyah; Harry Suharman; Syaiful Rahman Soenaria (Universitas Indo Global Mandiri)
Research on the effect of participatory budgeting and information asymmetry on budgetary slack still shows the inconsistency of conflicting results. This study aims to provide empirical evidence about the effect of participatory budgeting and information asymmetry on the tendency to make budgetary slack and the effect of moral equity as a moderating variable on the relationship between the variables of participatory budgeting, information asymmetry, and budgetary slack. The object of this research is all managers who work at PT. Pos Indonesia (Persero), PT. Pindad (Persero), PT. Kereta Api Indonesia (Persero) and PT. Len Industri (Persero), except for the board of directors. Data were collected using a research instrument in the form of a questionnaire with a total of 70 respondents. The analysis model used was moderated regression analysis (MRA - Moderated Regression Analysis). The results showed that: 1) Participatory budgeting had a positive and significant effect on budgetary slack as indicated by the coefficient value of participatory budgeting of 1.012 with a significance level of (4.999>1.998). 2) Information asymmetry has a significant negative effect on budgetary slack as indicated by the information asymmetry coefficient value of -1.7382 with a significance level of (-3.394 > - 1.998). 3). The results of the analysis show that moral equity is proven to be a moderator between participatory budgeting and information asymmetry towards budgetary slack in a positive direction. So it can be understood that budgetary slack can be reduced by increasing participatory budgeting and information asymmetry through moral equity.Keywords: Participatory Budgeting, Information Asymmetry, Budgetary Slack, Moral Equity